(untitled) - Radice, Francis (New York, 1997)
The book provides practice in the letter-writing skills neede for standard banking transactions, including motivation through progress and archievement tests; variety of text types fro comprehension and as production models; focus on cohesion, lexis, style and meaning; guided writing at sentence, paragraph and whole text level; opportunities for discussion as well as writing
Keywords: English language,English language,Listening; Spoken english,Problems, exercises, etc,Textbooks for foreign speakers,Problems, exercises, etc